Extreme runup events around a ship-shaped floating production, storage and offloading vessel in transient wave groups. (29th January 2021) - Chen, L.F.; Taylor, P.H.; Ning, D.Z.; Cong, P.W.; Wolgamot, H.; Draper, S.; Cheng, L.
Abstract: Abstract : Extreme wave runup around a simplified representative floating production, storage and offloading vessel hull with a vertical bow is studied using computational fluid dynamics, complemented by experimental and diffraction analysis. This is a highly nonlinear system involving large vessel motions and extreme surface waves, and the behaviour is important for offshore design and operations. A separation method based on phase manipulation is carried out to facilitate the extraction of harmonics associated with the Stokes expansion of nonlinear waves. The separation method is applied to numerical and experimental data, and found to work well even for a highly nonlinear wave field scattered from a freely floating ship-shaped body. It is found that both low- and high-frequency second harmonic components can lead to wave runup at significantly higher levels than predicted by a linear analysis, while the vessel motions are very close to linear. The nonlinearity in the local wave field rather than vessel motion is key for the excitation of nonlinear extreme runup.